The Influence Of Debt To Equity Ratio And Return On Asset To Conservatism Value Study At The Sector Of Consumer Goods Manufacture Listed In Indonesia Stock Exchange Periode 2013 – 2017 - Yusril Yusril; Della Indah Puspita Ningrum (Jurnal Ekonomi dan Bisnis, 2023)
The aim of the project is to analyze The Influence of Debt to Equity Ratio and Return on Asset to Conservatism Value Study at the Sector of Consumer Goods Manufacture listed in Indonesian Stock Exchange periode 2013 – 2017. This project used jenuh sampling techniques. Hence, the population of this project are used as a sample, Therer are 125 population and sample. The analysis method used are multiple linier regression. Data analysis used software IBM SPSS versi 25. In general the analysis shows that Debt to Equity Ratio does not has significant influence to conservatism value, the comparison are (0.104 > 0.05), and Return On Asset result shows negative influence to conservatism value, it is about (0.000 < 0.05) and has the value of the regression coefficient – 0.444 which mean the more Return on asset goes up than Conservatism Value goes down. Simultaneous test result suggests Debt to Equity Ratio and Return on Asset influence to conservatism value with comparison (0.000 < 0.005).